2011
DOI: 10.1111/j.1365-2133.2011.10397.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced subacute cutaneous lupus erythematosus: evidence for differences from its idiopathic counterpart

Abstract: DI-SCLE differs from idiopathic SCLE by virtue of distinctive cutaneous features, particularly the widespread presentation and the frequent occurrence of malar rash and bullous, EM-like and vasculitic manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 28 publications
5
92
1
3
Order By: Relevance
“…2 One study found that patients with drug-induced SCLE were older, had more extensive skin involvement and had an increased incidence of bullous, erythema multiforme-like and vasculitic lesions compared with individuals with idiopathic SCLE. 7 Photodistribution is characteristic as in our patient, and resolution occurred within a few months without treatment as noted in the literature. 8 Interestingly, our patient's unusual presentation of localised SCLE lesions on the hands may be explained by an occupational exposure to a topical drug, namely terbinafine.…”
Section: Discussionsupporting
confidence: 83%
“…2 One study found that patients with drug-induced SCLE were older, had more extensive skin involvement and had an increased incidence of bullous, erythema multiforme-like and vasculitic lesions compared with individuals with idiopathic SCLE. 7 Photodistribution is characteristic as in our patient, and resolution occurred within a few months without treatment as noted in the literature. 8 Interestingly, our patient's unusual presentation of localised SCLE lesions on the hands may be explained by an occupational exposure to a topical drug, namely terbinafine.…”
Section: Discussionsupporting
confidence: 83%
“…However, Bonsmann et al [10 ]suggested that the involvement of the lower extremities might indeed indicate DI-SCLE, as in our case 1 and case 3. Marzano et al [11] reviewed 11 out of 90 cases of non-PPI DI-SCLE, and concluded that the histopathological and immunological characteristics of idiopathic and DI-SCLE are similar, but that DI-SCLE differs from idiopathic SCLE by virtue of distinctive clinical features, namely the widespread presentation and the frequent occurrence of bullous, targetoid and vasculitic manifestations distinctive in the drug-related variant of SCLE (not evident in our 3 cases).…”
Section: Discussionmentioning
confidence: 99%
“…Another big challenge is to differentiate drug-induced SCLE from idiopathic SCLE. Marzano et al [11] reported that drug induced-SCLE differs from idiopathic SCLE by virtue of distinctive cutaneous features, particularly the widespread presentation and the frequent occurrence of malar rash and bullous, EM-like, and vasculitic manifestations.…”
Section: Clinical Featuresmentioning
confidence: 98%